2003
DOI: 10.1074/jbc.m211874200
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Kinesin Motor KIF1A with the Multimodular Protein Liprin-α

Abstract: Liprin-␣/SYD-2 is a multimodular scaffolding protein important for presynaptic differentiation and postsynaptic targeting of ␣-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid glutamate receptors. However, the molecular mechanisms underlying these functions remain largely unknown. Here we report that liprin-␣ interacts with the neuron-specific kinesin motor KIF1A. KIF1A colocalizes with liprin-␣ in various subcellular regions of neurons. KIF1A coaccumulates with liprin-␣ in ligated sciatic nerves. KIF1A cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 54 publications
6
163
0
Order By: Relevance
“…Some studies suggest that GRIP1 anchors AMPARs at synapses or delivers AMPARs to dendrites through binding to kinesin heavy chain or liprin-α (7,25,32,33). Other studies rather suggest that GRIP1 retains AMPARs within intracellular compartments (22,34).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that GRIP1 anchors AMPARs at synapses or delivers AMPARs to dendrites through binding to kinesin heavy chain or liprin-α (7,25,32,33). Other studies rather suggest that GRIP1 retains AMPARs within intracellular compartments (22,34).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been proven that SYD-2 regulates the Liprin-α/SYD-2 is proposed to act as an intracellular anchor for RPTP signaling at synaptic junctions [9,31] , and it has been shown that Liprin-α/SYD-2 binds Rim, CAST/ERC and kinesin [10,[32][33] . In addition, for the possible functional link between SYD-2, LAR and Nidogen, reports indicated that SYD-2 might recruit other density components to facilitate its assemble, and the presynaptic activity of SYD-2 might be modulated by LAR-Nidofen interaction to secure the synaptic assembly [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…80 KIF1A kinesin motor is associated with liprina and liprin-a-interacting Rab3A-interacting molecules, assisting in kinesin-mediated neuronal transport. 81 The functional significance of liprin-a at the mammalian synapses is largely unknown. Liprin-a binds to receptor protein tyrosine phosphatase (Dlar), which suggests that liprin-a3 and Dlar are involved in the formation of presynaptic active zones.…”
Section: Discussionmentioning
confidence: 99%